Monofractal Characteristics of Traffic in Wireless Sensor Networks for Smart Grid - Ming-Yue Zhai (Sensors & Transducers, 2014)
Wireless sensor networks (WSNs) have extensive applications in the smart grid in recently years. The time series in WSNs in smart grid should be discussed by analysis method which is non-linear. The method of monofractal is used here. Self-similar Hurst parameter calculated by the algorithm of Rescaled Range Analysis (R/S) and fractal dimension are obtained, which confirm that the time sequences in WSNs for smart grid belong to the fractal sets and have the characteristic of self- similarity.